(untitled) - Blass, Laurie (Boston, 2007)
Quest Second Edition parallels and accelerates the process native-speaking students go through when they prepare for success in a variety of academic subjects. Quest helps students get "up to speed" in terms of both academic content and language skills..
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Textbooks for foreign speakers,Spoken English,Problems, exercises, etc.,Giáo trình dành cho người nước ngoài,Tiếng Anh giao tiếp,Bài tập và bài giải